Development and validation of a highly sensitive LC–MS/MS method for the determination of acacetin in human plasma and its application to a protein binding study - Kim, Sang-Bum; Lee, Taehun; Lee, Hun Seok; Song, Chung Kil; Cho, Hyun-Jong; Kim, Dae-Duk; Maeng, Han-Joo; Yoon, In-Soo (Archives of pharmacal research, 2016)
A highly sensitive bioanalytical method for the quantification of acacetin in human plasma was developed and comprehensively validated using liquid chromatography-tandem mass spectrometry (LC–MS/MS). A minimal volume of human plasma sample (20 μL) was prepared by simple deproteinization with 80 μL of acetonitrile. Chromatographic separation was performed using Kinetex C₁₈ column with an isocratic mobile phase consisting of water and acetonitrile (20:80, v/v) containing 0.1 % formic acid at a flow rate of 0.3 mL/min over a total run time of 2.0 min. Mass spectrometric detection was performed using multiple reaction-monitoring modes at the mass/charge transitions m/z 285.22 → 242.17 for acacetin and m/z 277.59 → 175.04 for chlorpropamide (internal standard). The calibration curve was linear over the range of 0.1–500 ng/mL with a lower limit of quantitation of 0.1 ng/mL. The coefficients of variation for both intra- and inter-day validation were less than 11.9 %, and the intra- and inter-day accuracy ranged from 96.8 to 108 %. Mean recovery of acacetin in human plasma was within the range of 91.5–95.6 %. This validated LC–MS/MS method was successfully applied to a human plasma protein binding study that indicated extensive and concentration-independent protein binding of acacetin in human plasma.